How to help aortic dissection survivors with recovery?: A health promotion program based on the comprehensive theory of health behavior change and literature review. Issue 7 (17th February 2023) - Lang, Xiaorong; Feng, Danni; Huang, Sufang; Liu, Yucheng; Zhang, Kexin; Shen, Xiaoxuan; Huang, Jingjing; Wang, Quan
Abstract : For aortic dissection survivors, health promotion can help them recover from the disease, which requires systematic program support. The aim of this study was to construct a health promotion program for aortic dissection survivors. Literature search, group discussion, and expert consultation were used. The Integrated Theory of Health Behavior Change was the theoretical basis of the program. Multiple medical-related databases were searched. Based on a literature search and group discussion, 3 primary items, 8 secondary items, and 34 tertiary items were formed. After 2 rounds of expert consultation (number of experts = 25), 3 primary items, 16 secondary items, and 54 tertiary items were retained. The authority coefficients of the 2 rounds of experts were 0.890 and 0.905, respectively. The Kendall W coefficient of the 2 rounds were 0.210 to 0.370 ( P < .05) and 0.221 to 0.378 ( P < .05), respectively. The mean importance value and coefficient of variation of each item were >3.5 and <0.25, respectively. The health promotion program constructed in this study was reasonable and scientific, which could provide a reference for clinical work.